(untitled) (Global Journal of Management and Business Research, 2016)
Bangladesh is a small low-mid-level country. Information and Communication Technologies are recognized as a powerful tool for socio-economic development. Nowadays technology confines this world into a small maze. Everything can be found in web. Yes, we are talking about online shopping; from land to dress everything can be sold or bought through online. So, online shopping become a trends in our busy corporate life and its impact has fallen in our country. This paper refers the challenges for the digital marketing of online shopping; or ecommerce or m-commerce. Also describe the present status of digital marketing and their impacts on the socio-economic development of the country. To sustain in today’s fast economy online shopping need excellent marketing mix to grow, introduce into consumers perception. Research will focus on as a bird eye view of constraints of marketing of this sector such as people’s perception, lack of efficient user, high price of electronics commodities.